Osteoarticular Infections Caused by Streptococcus pneumoniae in Children in the Post–Pneumococcal Conjugate Vaccine Era. Issue 12 (December 2017) - Olarte, Liset; Romero, Jose; Barson, William; Bradley, John; Lin, Philana Ling; Givner, Laurence; Tan, Tina; Hoffman, Jill; Hultén, Kristina G.; Mason, Edward O.; Kaplan, Sheldon L.
Abstract : Background: Pneumococcal osteoarticular infections (OAIs) are an uncommon manifestation of invasive pneumococcal disease (IPD). We describe the demographic characteristics, hospitalization rate, serotype distribution and antibiotic susceptibility of children with pneumococcal OAI over a 16-year period. Methods: We identified patients ⩽18 years old with pneumococcal OAI at 8 children's hospitals in the United States (2000–2015). Pneumococcal isolates were collected prospectively. Serotyping and antibiotic susceptibility were performed in a central laboratory. Results: We identified 97 (3.3%) patients with pneumococcal OAI out of 2943 patients with IPD. Over 60% of the children were <2 years old. Septic arthritis (56.7%, 55/97) was the most common pneumococcal OAI, followed by osteomyelitis (25.8%, 25/97) and septic arthritis with concomitant osteomyelitis (17.5%, 17/97). Hospitalization for pneumococcal OAI overall decreased from 6.8 [95% confidence interval (CI): 5.2–8.6] to 4.4 (95% CI: 3.0–6.3) per 100, 000 admissions from 2000–2009 to 2010–2015 (–35%, P = 0.05). Hospitalization for pneumococcal OAI caused by PCV13 serotypes decreased from 4.6 (95% CI: 3.4–6.2) to 0.9 (95% CI: 0.3–1.9) per 100, 000 admissions from 2000–2009 to 2010–2015 (–87%, P < 0.0001). Overall, 12% of isolates had a penicillin minimal inhibitory concentration> 2 µg/mL, 3% a ceftriaxone minimal inhibitory concentration> 1 µg/mL and 15% were clindamycin resistant; these proportions remained unchanged after the introduction of PCV13. Serotypes 19A and 35B were responsible for penicillin and ceftriaxone nonsusceptible isolates in 2010–2015. Conclusions: Pneumococcal OAI represents 3% of all IPD, affecting mainly healthy infants and young children. Hospitalization for pneumococcal OAI caused by PCV13 serotypes dramatically decreased (–87%) after the introduction of PCV13. Abstract : Supplemental Digital Content is available in the text.